2015
DOI: 10.1177/0363546515579636
|View full text |Cite
|
Sign up to set email alerts
|

Pitching Performance and Longevity After Revision Ulnar Collateral Ligament Reconstruction in Major League Baseball Pitchers

Abstract: MLB pitchers who undergo UCL-R have a low rate of return to MLB play and have shortened careers after return. Pitchers who returned to the MLB level maintained performance in several statistics such as earned run average and walks/hits per innings pitched; however, pitchers returned with a significantly decreased workload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
91
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 21 publications
1
91
0
Order By: Relevance
“…Interestingly, the rate of ulnar nerve complications was similar to that observed for primary UCL reconstruction. Marshall et al 74 compared 33 Major League pitchers who underwent revision UCL reconstruction with 33 age-matched controls, and found a low rate of return to sport (66%) and shortened careers after return to sport (minus 0.8 years). Although various statistics of performance (earned run average, walks/hits per innings pitched) were maintained, pitchers returned with a significantly decreased workload, that is, number of innings pitched 74.…”
Section: Considerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the rate of ulnar nerve complications was similar to that observed for primary UCL reconstruction. Marshall et al 74 compared 33 Major League pitchers who underwent revision UCL reconstruction with 33 age-matched controls, and found a low rate of return to sport (66%) and shortened careers after return to sport (minus 0.8 years). Although various statistics of performance (earned run average, walks/hits per innings pitched) were maintained, pitchers returned with a significantly decreased workload, that is, number of innings pitched 74.…”
Section: Considerationmentioning
confidence: 99%
“…Marshall et al 74 compared 33 Major League pitchers who underwent revision UCL reconstruction with 33 age-matched controls, and found a low rate of return to sport (66%) and shortened careers after return to sport (minus 0.8 years). Although various statistics of performance (earned run average, walks/hits per innings pitched) were maintained, pitchers returned with a significantly decreased workload, that is, number of innings pitched 74. Liu et al 71 recently presented similar results in a retrospective analysis of publicly available Major League data 71…”
Section: Considerationmentioning
confidence: 99%
“…Although their model correctly classified about two-thirds of the subjects, it only explained about 20% of the variance in UCL reconstruction surgery, underscoring the difficulty of accurately predicting injuries by identifying individual risk factors. 1 As UCL reconstructions have become more common in professional pitchers, the specter of revision surgery has surfaced as a worrisome possibility, 3,6,8 Using data from 4 decades of MLB history, they studied 154 pitchers who returned from UCL reconstruction for at least 1 full season of pitching, of whom 19 went on to revision surgery. In brief, they found no difference between the groups according to multiple pitching metrics, including the numbers of pitches thrown and innings pitched, both in the season after UCL reconstruction and in their subsequent careers.…”
mentioning
confidence: 99%
“…Following groundbreaking studies that documented the rate of return and level of competition achieved after surgery, 3,12 more recent authors have utilized results from their own patients, 1,18 publicly available statistics, 7,11,13,15,16 and data collected by MLB itself 4 to analyze the performance of pitchers with reconstructed elbows in greater detail. Results of these studies have varied.…”
mentioning
confidence: 99%
“…''Pitching Performance After Revision Ulnar Collateral Ligament Reconstruction in Major League Pitchers,'' also in this issue of AJSM, addresses this question. Using publicly available data, Marshall et al 16 identified 33 MLB pitchers who underwent revision UCL reconstruction between 1996 and 2012. Any revision operation is rarely as successful as a primary procedure, so it is not too surprising that only 66% returned to play in MLB, compared with the more than 80% return rate reported by others for primary UCL reconstruction.…”
mentioning
confidence: 99%